Comparative resource-environment-economy assessment of coal- and oil-based aromatics production. (August 2022) - Li, Junjie; Zhang, Yueling; Yang, Yanli; Zhang, Xiaomei; Zheng, Yonghong; Qian, Qi; Tian, Yajun; Xie, Kechang
Abstract: Aromatics is an important chemical material with a greatly increasing demand across the world. However, its production normally depends on the conventional oil-based naphtha to aromatics (OBNTA) route, resulting in difficulty for oil-shortage countries to meet local demand. The coal-based methanol to aromatics (CBMTA) route is considered a promising alternative to diversify the production of the aromatic whereas its industrial competitiveness relative to the OBNTA route has been not fully assessed at a resource-environment-economy level. This study proposes a comprehensive assessment framework that integrates the life cycle assessment, technical-economic analysis, and entropy weight method to quantify and compare the resource consumption, environmental emission, and economic benefit of the CBMTA and OBNTA routes. The operating data for the industrialized plants, economic data of China's market, and background data from the LCA database are taken as the input of the assessment framework. The sensitivity to operating and economic data and uncertainty caused by original data, allocation procedures, and feedstock sources are considered. The assessment shows that the CBMTA route scores worse comprehensive competitiveness than the OBNTA route due to its higher resource consumption and environmental emission. However, it performs well in economic benefit at Chinese current prices, which may attract more attention from investors. Based on the assessment, a SWOT analysis is carried out to further address resource-environment-economy tradeoffs. The analysis shows a considerable prospect of the CBMTA route thanks to all kinds of external opportunities, which however need to vigorously promote cleaner production policies and specific investment strategies tailored to local resource-environment-economy conditions. The current work can help policymakers, stakeholders, and investors better understand the multi-dimensional tradeoffs and make decisions. Highlights: An assessment framework integrating LCA, TEA, and EWM is proposed. Resource-environment-economy performances are compared. A SWOT analysis of the CBMTA and OBNTA routes is conducted. The CBMTA route performs better in economic benefit at the current prices. The CBMTA route is considered a competitor of the OBNTA route in China.